Wood Characteristic of Superior Sengon Collection and Prospect of Wood Properties Improvement through Genetic Engineering - N. Sri Hartati; Enny Sudarmonowati; Widya Fatriasari; Euis Hermiati; Wahyu Dwianto; Rumi Kaida; Kei’ichi Baba; Takahisa Hayashi (Masyarakat Peneliti Kayu Indonesia, 2010)
Many tree breeding programs ranging from conventional to molecular genetics approach were applied to produce clone or tree genetic industrially desirable wood. This study was aimed to evaluate the wood properties of selected sengon (Paraserianthes falcataria) tree which has high score of growth parameter and stem form and to evaluate stem properties of transgenic sengon and mangium (Acacia mangium) overexpressing wall hydrolases. Physical and chemical wood properties including basic density, shrinkage and thickness swelling, estimated stand volume, cellulose, lignin and water content were examined for two selected plus tree sengon namely PI and PII, which were grown at Germ Plasm Collection Garden of Research Centre for Biotechnology - LIPI. Both of two sengon tree has high value of estimated stand volume and basic density (0.43 and 0.49 g/cm3). The PII tree has lower lignin and water content than P I. Cellulase overexpression in sengon and xyloglucanase overexpression in mangium could alter stem cell walls composition. Transgenics mangium stem have higher cellulose content (37.70 53.64%) and lower hemicelluloses content (30 40%) than the wild type.